PERENCANAAN PAJAK DALAM PENYUSUTAN AKTIVA TETAP PADA PT. SEGARA HERO SAKTI SAMARINDA - Ferie, Jheef Ferie (EKONOMIA, 2018)
The purpose of the study is to determine differences in straight-line depreciation method and double declining balance in determining the profit that will affect the tax burden, in order to make good and efficient tax planning done by PT. Segara Hero sakti. The problems outline formulated as follows, is there a significant difference between the straight-line depreciation method and the double declining balance in determining the income tax expense to be paid by PT. Segara Hero Sakti?Basic Theory in this study is financial accounting that focuses on the financial statements, especially on the fixed assets lists of PT. Segara Hero Sakti in using depreciation method and tax regulations. The hypothesis in this study is that there is a significant difference between straight-line depreciation method and double declining balance in determining income tax expense that will be paid by PT. Segara Hero SaktiThe analytical tools used in this research are straight-line method and double declining balance method, then comparing the methods calculation result using paired T-Test contained in SPSS data processing program for significance test. The calculation also includes discount factor, the amount of present value and current tax rate.The result of analysis and discussion shows that there is a significant difference between straight-line method and double declining balance in determining income tax (PPH) burden. Depreciation method calculation to fixed assets of PT. Segara Hero Sakti Samarinda using double declining balance method can assist the management in tax planning. The management can save income tax cost compared from the previous method using straight-line method in depreciation expense calculation. Therefore, the research supports the hypothesis, then the hypothesis is accepted.Â